Synthesis and characterization of the poly-(sorbitol co-citrate adipate) a biopolymer aiming to obtain a biomaterial - Torres, Adriano de Ulhôa; Sarrouh, Boutros; Lofrano, Renata Carolina Zanetti (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2023)
This work describes the synthesis and physicochemical and microstructural characterization of poly(sorbitol adipate co-citrate) with the aim of obtaining a sustainable biopolymer derived from renewable and non-toxic sources intended for applications such as biomaterial. Polymerizations at three different ratios of sorbitol and adipic and citric acids (A, B and C) were studied. The materials were characterized by X-ray diffraction (XRD), infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) techniques. Such analyses showed that only in state C was an amorphous copolyester obtained, with different particle sizes and visibly hard and with a translucent yellowish color.